2014
DOI: 10.1136/bmj.g5740
|View full text |Cite
|
Sign up to set email alerts
|

Effect of providing free glasses on children's educational outcomes in China: cluster randomized controlled trial

Abstract: Objective To assess the effect of provision of free glasses on academic performance in rural Chinese children with myopia.Design Cluster randomized, investigator masked, controlled trial.Setting 252 primary schools in two prefectures in western China, 2012-13.Participants 3177 of 19 934 children in fourth and fifth grades (mean age 10.5 years) with visual acuity <6/12 in either eye without glasses correctable to >6/12 with glasses. 3052 (96.0%) completed the study.Interventions Children were randomized by scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
253
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(276 citation statements)
references
References 22 publications
9
253
3
Order By: Relevance
“…Multimedia educational interventions, when used alone, have been unsuccessful in increasing acceptance of low-cost comprehensive eye examinations 24 or cataract surgery 25 or in promoting purchase of children's spectacles. 26 Although a focus group study 27 indicated that patients in rural China may not be comfortable with direct cash payments to encourage medical compliance, Ma et al 28 have reported that the offer of free spectacles doubled spectacle wear at a later unannounced examination, which is consistent with improved adherence observed in the present study. It appears that the offer of free medical goods, such as medication and spectacles, may be particularly effective in this setting in changing behavior and gives the added advantage of direct clinical benefit to patients.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Multimedia educational interventions, when used alone, have been unsuccessful in increasing acceptance of low-cost comprehensive eye examinations 24 or cataract surgery 25 or in promoting purchase of children's spectacles. 26 Although a focus group study 27 indicated that patients in rural China may not be comfortable with direct cash payments to encourage medical compliance, Ma et al 28 have reported that the offer of free spectacles doubled spectacle wear at a later unannounced examination, which is consistent with improved adherence observed in the present study. It appears that the offer of free medical goods, such as medication and spectacles, may be particularly effective in this setting in changing behavior and gives the added advantage of direct clinical benefit to patients.…”
Section: Discussionsupporting
confidence: 82%
“…b Three patients were unavailable for follow-up at 2 weeks and 4 patients were unavailable for follow-up at 1 mo after surgery. The result of the current study, in which adherence was nearly doubled with an intervention costing less than US$25 per patient, may be compared with other reports [24][25][26][27][28] on interventions to enhance uptake of or adherence with eye care in rural China. Multimedia educational interventions, when used alone, have been unsuccessful in increasing acceptance of low-cost comprehensive eye examinations 24 or cataract surgery 25 or in promoting purchase of children's spectacles.…”
Section: Discussionmentioning
confidence: 80%
“…1 If not treated, refractive error is associated with loss of visual function 2 and reduced educational performance in children. 3 Though refractive error can be safely 4 and inexpensively managed with glasses, as few as 1 in 6 children needing spectacles have them in rural parts of the developing world. 3 Spectacle distribution programs for children can lead to normalization of visual function 5 and trial-proven, significant improvements in educational outcomes.…”
mentioning
confidence: 99%
“…3 Though refractive error can be safely 4 and inexpensively managed with glasses, as few as 1 in 6 children needing spectacles have them in rural parts of the developing world. 3 Spectacle distribution programs for children can lead to normalization of visual function 5 and trial-proven, significant improvements in educational outcomes. 3 However, programs in China, 3 Mexico, 6 and Africa 7 have reported poor compliance with free spectacles, with rates of observed, short-term wear at unannounced visits ranging from 13% to 41%.…”
mentioning
confidence: 99%
“…Study methods including institutional review board approvals and consent have been described elsewhere. 1 The study was carried out in Yulin prefecture, Shaanxi, and Tianshui prefecture, Gansu Province, which are nearby areas. Shaanxi's gross domestic product per capita is $US6108 and was ranked 14th among China's 31 administrative regions in 2012, while Gansu is the second-poorest province in the country (per capita gross domestic product of $US3100).…”
mentioning
confidence: 99%